Analisis Pengendalian Internal Atas Persediaan Barang Dagang Pada PT TDM Sukabumi - Putri, Annisa Ayunda (Universitas Muhammadiyah Tangerang, 2021)
Trading companies generally buy merchandise in a form that is ready to be resold without changing from its original form. Merchandise inventory is an important element in the operational activities of a company. Hence,it requires effective and efficient control and management of merchandise inventory in order to prevent fraud or damage to the inventory. The purpose of this study is to analyze to determine the inventory accounting system of merchandise and internal controls applied to PT TDM Sukabumi. The method used in this study is descriptive qualitative method. the data collected used in the study are primary data obtained directrly by observation and interview and secondary data through documentation and study of literature. the data analysis technique carried out in the study are data reduction, data display and conclusion drawing.The results of the research that have been carried out show the system and procedures for managing merchandise inventory that have been applied to PT TDM Sukabumi have been adequate. The company records its merchandise inventory using perpetual method and appraises its merchandise inventory using FIFO inventory cost method but the internal control in inventory function still has not properly effective.